ESTUDO DAS COMPETÊNCIAS DO ADMINISTRADOR DE EMPRESAS: UMA REVISÃO DE LITERATURA - Ribeiro, Alecir Vitorino (2012)
This research aimed at a comparative analysis between the skills traditionally developed in schools of business administration, with contemporary demands. With respect to methodology, the research is characterized as exploratory, because it was developed through literature review. The base is the qualitative selection of material relevant to their interests. The methodological procedures used were content analysis of articles, books, dissertations and scientific production and doctoral theses. It was used as a methodology, observation by the author in teaching practices in undergraduate courses in business administration. Conclusions were obtained as: requirements, in terms of skills to the administrator, evolved into the dynamics of the new social order, on application of the fundamentals of social responsibility and sustainability; wonders pragmatism of linear thinking, binary optics, which already does not stand a society that requires parameters of production and operation less impacting to life. Finally, it outlines the suggestion for further research, definition models to support organizational decisions considering the complexity of contemporary management.